Diffusion model to describe osteogenesis within a porous titanium scaffold. Issue 2 (25th January 2016) - Schmitt, M.; Allena, R.; Schouman, T.; Frasca, S.; Collombet, J.M.; Holy, X.; Rouch, P.
Abstract : In this study, we develop a two-dimensional finite element model, which is derived from an animal experiment and allows simulating osteogenesis within a porous titanium scaffold implanted in ewe's hemi-mandible during 12 weeks. The cell activity is described through diffusion equations and regulated by the stress state of the structure. We compare our model to (i) histological observations and (ii) experimental data obtained from a mechanical test done on sacrificed animal. We show that our mechano-biological approach provides consistent numerical results and constitutes a useful tool to predict osteogenesis pattern.